KEWENANGAN PEMERINTAH DAERAH DALAM URUSAN PEMERINTAHAN DI BIDANG LINGKUNGAN HIDUP DALAM PENYELESAIAN KERUSAKAN LINGKUNGAN HIDUP AKIBAT PROYEK KERETA CEPAT WHOOSH DI KABUPATEN PURWAKARTA - Oktopiani, Leni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
The development of the Whoosh High Speed Railway in Bunder Village, Purwakarta Regency, has raised serious concerns regarding environmental damage. Despite the authority of the Regency Government to address such environmental issues, the full responsibility for this project lies with the Central Government, thereby constraining the local government's authority in managing environmental affairs within the region. In light of these issues, this research aims to analyze the authority of the local government in addressing the environmental impacts of the Whoosh High-Speed Train development in Purwakarta Regency. The research method employed is descriptive research with a qualitative approach, utilizing observation, interviews, and documentation. The findings indicate that existing regulations are not sufficiently specific to address the environmental impacts of this project, resulting in a lack of coordination and potential harm to the environment and local communities. The restriction of local authority by the Central Government also affects environmental control efforts at the regional level. Evaluation of the implementation of regional autonomy reveals that Purwakarta Regency has not fully succeeded, as several factors such as finances and equipment remain unmet. This evaluation is crucial for understanding challenges and maximizing the implementation of regional autonomy in Purwakarta Regency.